Sustainable Development Of Irrigation Infrastructure in Vietnam: A Theoretical Framework - Nguyen-Duc, Thanh; Tran Tho, Dat (International Journal of Sustainable Construction Engineering and Technology, 2025)
Investing in the sustainable development of irrigation infrastructure is the best way to address the issue of climate change, which is still uncertain in Vietnam. A convenient sampling was conducted to gather relevant literature for analysis. 150 publications including journal articles, books, book chapters, conference papers and technical reports have been collected and analysed in this research study. The keywords found were visualised with VoSViewer. By integrating the keywords' shared interests, the publications can be arranged to three clusters based on keyword frequency: (1) sustainable development and investment; (2) irrigation infrastructure investment; and (3) irrigation infrastructure investment efficiency. The study confirms the need to examine the investment efficiency of these projects by providing a summary of previous research on the sustainable development of irrigation infrastructure. Subsequently, a theoretical framework is constructed on the efficacy of sustainable irrigation infrastructure development, which is influenced by nine key factors: (1) Natural conditions; (2) Institutions and policies; (3) Politics, socio-culture; (4) Economy; (5) Science and technology; (6) Human; (7) Management; (8) Project finance; (9) Operation. A future research on the sustainable development of irrigation infrastructure can focus on one or a combination of the factors. A holistic research study may need to address all of the factors.